Kajian Akhlak Akhlak Kepada Kedua Orang Tua Dalam Al-Qur'an (Kajian Tafsir Tematik): Indonesia - Rohim Hidayat; Muh. Tasrif (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2025)
This article discusses morals towards both parents, with a special focus on being devoted to both parents as commanded in Islam, being polite to both parents, both in words and actions according to the traditions of society, so that both parents feel happy with their children, fulfilling both of their needs as appropriate according to the child's ability. This does not include anything that can eliminate personal freedom, household affairs or types of work related to the child's personality, religion or country. This is because being good to both parents does not require neglecting personal rights. The Qur'an teaches morals towards both parents. Being devoted to parents who have died includes turning them towards the Qibla, guiding them to say tawheed, reciting the Yasin letter, being humble towards both of them, even though they are non-Muslims they still have to be filial as long as what they do does not associate partners with Allah SWT. This remains relevant and applicable in modern life as a solution to various social problems related to morals towards parents.